Community Response to the Impact of Thunderstorm Asthma Using Smart Technology - Ala AlQuran MPH; Mehak Batra MDS; Nugroho Harry Susanto PhD; Anne E. Holland PhD; Janet M. Davies PhD; Bircan Erbas PhD; Edwin R. Lampugnani PhD (Allergy & Rhinology, 2021)
Background The most severe thunderstorm asthma (TA) event occurred in Melbourne on the 21st November 2016 and during this period, daily pollen information was available and accessible on smart devices via an App. An integrated survey within the App allows users to self-report symptoms. Objective To explore patterns of symptom survey results during the period when the TA event occurred. Methods Symptom data from the Melbourne Pollen Count and Forecast App related to asthma history, hay fever symptoms, and medication use was explored. A one-week control period before and after the event was considered. Chi-square tests and logistic regression were used to assess associations between sex, age, symptoms, and medication use. Results Of the 28,655 responses, during the 2016 pollen season, younger (18 to 40 years) males, with no hay fever and no asthma were the most single and regular responders. During the TA event for new users, sex was only significantly associated with hay fever ( p  = 0.008) of which 60.2% of females’ responses reported having hay fever, while 43% of males’ responses did not. Those with mild symptoms peaked during the TA event. Conclusions Many individuals completed the survey on the app for the first time during the TA event indicating the potential of digital technologies to be used as indicators of health risk among populations at risk of TA events.